Pharyngolaryngectomy with thoracoscopic esophagectomy via the left thoracic approach for cervical esophageal cancer with right aortic arch: Case report. Issue 3 (27th January 2022) - Nagano, Shotaro; Kitadani, Junya; Ojima, Toshiyasu; Hayata, Keiji; Katsuda, Masahiro; Goda, Taro; Takeuchi, Akihiro; Tamagawa, Shunji; Hijiya, Masayoshi; Tachibana, Satsuki; Hotomi, Muneki; Asamura, Shinichi; et al.
Abstract: We performed pharyngolaryngectomy with thoracoscopic esophagectomy via the left thoracic approach and reconstruction of the elongated gastric conduit with microvascular anastomosis for an 83‐year‐old male patient with esophageal cancer and right aortic arch. For such cases, a surgical approach via the left thoracic cavity is rational, and cases of pharyngolaryngectomy with thoracoscopic esophagectomy require a long reconstruction organ. Also, in cases of right aortic arch, a longer reconstruction route is made to avoid Kommerell's diverticulum. The patient had laryngeal cancer and was diagnosed with cervical esophageal cancer and preoperative computed tomography revealed right aortic arch. There were no complications after surgery, and food intake was good. Pharyngolaryngectomy with thoracoscopic esophagectomy via the left thoracic approach and reconstruction of the elongated gastric conduit with microvascular anastomosis is suggested to be a safe and feasible technique for cases of cervical esophageal cancer with right aortic arch.